Movie recommendation system using clustering mining with Python. Issue 4 (July 2021) - Sadhasivam, Jayakumar; Cera, Juan Manuel; Deepa, R; Satheshkumar, K; Muthukumaran, V; Satheesh Kumar, S; Angeline Kavitha, M
Abstract: The research we are pursuing here is about building a system which we will use and mine a movie review database using concepts of statistics like Euclidean Distance algorithm. This will help us determine similar review according to the ratings. What we plan on achieving through this approach is to analyze the reviews to suggest a suitable critic according to one's preferences and one's taste. We will do this according to the review we select and our algorithm which we use upon it. This algorithm will be the key to find those similar reviews. We are going to use Python programming to program this experiment. We have chosen to pursue this because of not the reviewers being incorrect or correct but merely different according to their preferences and their lean towards a certain genre and we know that a reviewer should also match the taste of the person who want to feel benefited of the review itself. So, we plan to make system that could help with that.